SOME ISSUES THE INTRODUCTION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE TEACHING OF CHEMISTRY - Kokanbayev Ikramzhon Ibrokhimovich (Galaxy International Interdisciplinary Research Journal, 2023)
A huge technical achievement of the 20th century is the effectiveness of computerized education. Today it is difficult to imagine education without digitization, because through it the teacher’s activities are simplified, the level of learning efficiency increases. Various information and communication technologies are used in education, which not only facilitate the work of teachers, but also create great opportunities for teaching. Using the capabilities of a virtual laboratory in teaching chemistry not only increases students’ interest in the subject, but also significantly affects the level of their development.